What factors of -33 add up to -8?
-11 + 3 = -8 and -11*3 = -33
y^2 - 8y - 33 = 0
(y-11)(y+3) = 0
y - 11 = 0 or y + 3 = 0
y = 11 or y = -3
2006-11-08 11:33:09
·
answer #1
·
answered by MsMath 7
·
3⤊
4⤋
y^2 -8y -33 can be factorized into (y-11)(y+3). Since this must equal zero, then either y - 11 = 0, or y + 3 = 0. Therefore, y must either be 11, or -3.
2006-11-08 19:34:09
·
answer #2
·
answered by Scythian1950 7
·
2⤊
0⤋
y^2 -8y -33 can be factorized into (y-11)(y+3). Since this must equal zero, then either y - 11 = 0, or y + 3 = 0. so, y must either be 11, or -3.
good luck with your gay algerbra
2006-11-08 19:38:12
·
answer #3
·
answered by Grilled cheese lover 2
·
1⤊
1⤋
y=11
2006-11-08 19:35:11
·
answer #4
·
answered by darlinga 1
·
0⤊
2⤋
-it is always a safe bet to use the quadratic formula:
x= ( 8 +- sqrt(64-4(-33)) /2
with the help of a calculator you find that
x=11 or x= -3
2006-11-09 15:23:22
·
answer #5
·
answered by locuaz 7
·
1⤊
1⤋
y^2-8y-33=0
(y-11)(y+3)=0
y-11=0 or y+3=0
y={-3,11}
2006-11-08 19:34:17
·
answer #6
·
answered by moonfreak♦ 5
·
1⤊
0⤋
That problem is already simplified as far as it will go. Sorry!
2006-11-08 19:34:16
·
answer #7
·
answered by eden 2
·
0⤊
2⤋